THE PARENTS' KNOWLEDGE ON THE CARE PROCESS THROUGH PLAY - Aderlaine da Silva Sabino; Arinete Véras Fontes Esteves; Ana Paula Pessoa de Oliveira; Marcos Vinícius Gusmão da Silva (Universidade Federal do Paraná, 2018)
Objective: verify how the parents and/or legal caregivers of hospitalized children perceive playing as a dimension of Nursing care. Method: qualitative, descriptive, exploratory and prospective study, using theme/category-based analysis. A semistructured interview was held at a Children's Hospital of reference in the State of Amazonas in January 2016. The participants were 22 parents between 18 and 50 years of age. The thematic categories "Meaning of play and playing", "Importance of the toy during playing practice for hospitalized children" and "Care while playing" emerged from the analysis. Results: the parents acknowledged the importance of playing during the care process in pediatric contexts, but did not envisage the activity as part of the professionals' care plan, so that the child's singularity can be fully respected in that sense. Conclusion: the professionals need qualification and awareness raising to use play in their care practice.